The power of the powerless teachers: discipline in the contemporary school - Páchová, Anna (e-Pedagogium, 2023)
Discipline in school has historically been an integral part of educational practice. However, with the emergence of alternative teaching trends and the emphasis on constructivist teaching the call to weaken the power of the school and the authority of the teacher emerge. The text focuses on the issue of qualitative paradigm shifts in the issue of pupil discipline. The analysis of discipline in the Czech environment was based on a comparison of the traditional approach to teaching mathematics with the approach of teaching according to the so-called Hejný method, which is characterized by a paradigm of lower teacher authority. The text answers how disciplinary interventions look like in mathematics classes taught in the traditional way (T-classes) and in the Hejný approach (H-classes). The data source was video recordings of mathematics lessons in eight classrooms. The analysis showed that discipline plays a significant role in both approaches. What differed, however, were the forms of discipline, or rather their explicitness. A high degree of explicitness of the requirements was typical in the T-classes, while in the H-classes a non-explicit form with an emphasis on the requirement of self-discipline was more typical. The text concludes by considering whether these differences are important, or whether the H-method is more of a formal oversight that is consistent with the demands of contemporary public discourse.
Keywords: discipline; school; disciplinary interventions; Hejný's approach; power.